The volume and source of cyberabuse influences victim blame and perceptions of attractiveness. (March 2019) - Scott, Graham G.; Wiencierz, Stacey; Hand, Christopher J.
Abstract: Cyberabuse is an escalating problem in society, as opportunities for abuse to occur in online public domains increase. Such acts are often defined by the frequency of abuse, and in many cases multiple individuals play a part in the abuse. Although consequences of such acts are often severe, there is typically little public sympathy/support for victims. To better understand perceptions of victims of abusive online acts, we manipulated the Volume (low, high) and Source (same-source, multi-source) of abusive posts in artificially-manipulated Facebook timelines of four fictitious 'victims'. One hundred and sixty-four participants [United Kingdom-based; aged 18–59] rated 'victims' on measures of direct victim blame (DVB) and perceived social-, physical- and task-attractiveness. Results revealed significant Volume × Source interactions on DVB and social-attractiveness ratings. Few abusive posts authored by a single source yielded higher DVB and lower social-attractiveness ratings. Strong correlations between attractiveness and DVB were observed. We propose that our results could be due to an observer desensitization effect, or that participants interpreted the posts as indicative of friendly 'teasing' or 'banter' within an established social relationship, helping to explain why victims of online abuse often receive little sympathy or support. Highlights: 'Victim-blaming' was highest when cyberbullying was low-volume from a single source. 'Victim-blaming' was lowest when cyberbullying was high-volume from a single source. 'Victims' were rated least socially-attractive if bullied rarely by a single source. 'Victims' were rated most socially-attractive when bullied often by a single source. 'Victim' physical attractiveness ratings were not altered by abuse volume or source.